Service quality and customer service performance - the case of Vietnam joint stock commercial bank for private enterprises : Luận văn ThS. Kinh doanh và quản lý: 60 34 05 - Nguyễn, Quỳnh Trang (Đại học Quốc gia Hà Nội, 2017)
77 p. + CD-ROM